(untitled) (Research, Society and Development, 2022)
Water is part of several chemical, physical, and biological processes necessary for the maintenance of life. The use of contaminated or non-potable resources can cause health problems to the population. The water standards considered suitable for human consumption are described in Ordinance GM/MS nº 888/2021 of the Ministry of Health. The objective of this work was to evaluate the water of public use spouts in the municipality of Poços de Caldas, Minas Gerais. In this regard, the water from four spouts used by the population was evaluated. Chemical reagents from the EcoKit® product were used to verify the physicochemical variables (turbidity, dissolved oxygen, pH and concentrations of orthophosphate, ammonia, nitrates, and nitrites). All samples presented the results of turbidity, ammonia, nitrate, and dissolved oxygen in accordance with current legislation. Collection points 3 and 4 showed pH values ​​below the range defined as adequate in the current legislation for human consumption (between 6 and 9.5) and the concentration of orthophosphate was above the acceptance limit according to the Resolution 357/2005 of CONAMA (0,20 mg/L), being unsuitable for human consumption. In this sense, it is important to adopt public policies aimed to monitore, in addition to the development of adequate sanitation and sanitation projects to guarantee the quality of the water supplied to the population. Finally, it is necessary to disseminate information to consumers about practices and attitudes that make the use of water resources safer.